Metal Complexes of Aroylhydrazones: Preparation and Structural Characterization - H.K. Duggal, (Miss); Agarwala, B.V. (Asian Journal of Chemistry, 2010)
Four aroylhydrazone Schiff bases viz. 2-furaldehyde-p-chlorobenzoylhydrazone (fcbH), p-methoxybenzaldehyde p-chlorobenzoylhydrazone (mbcbH), p-methoxybenzaldehyde salicyloylhydrazone (mbsH) and 2-furaldehyde salicyloylhydrazone (fsH) are prepared, Fifteen complexes of the general formula [ML2(H2O)2] and three of general formula [ML2] have been synthesised where LH ═ fcbH; mbcbH, mbsH, fsH and M ═ a bipositive cation. From the results of chemical analysis, magnetic susceptibility measurements at different current, ir, drs and thermal studies the mode of chelation of the ligand and geometry of the complex molecules are assigned. Consequently Co(II)-mbsH and the diamagnetic Ni(II)-mbsH, Ni(II)-fsH complexes are formulated as square pyramidal whereas an octahedral environment around each metal is proposed in rest of the bispositive aroylhydrazone complexes.